Translational studies of exosomes in sports medicine – a mini-review - Huang, Haoqiang; Chen, Peng; Feng, Xinting; Qian, Yinhua; Peng, Zhijian; Zhang, Ting; Wang, Qing (Frontiers in Immunology, 2024)
This review in sports medicine focuses on the critical role of exosomes in managing chronic conditions and enhancing athletic performance. Exosomes, small vesicles produced by various cells, are essential for cellular communication and transporting molecules like proteins and nucleic acids. Originating from the endoplasmic reticulum, they play a vital role in modulating inflammation and tissue repair. Their significance in sports medicine is increasingly recognized, particularly in healing athletic injuries, improving articular cartilage lesions, and osteoarthritic conditions by modulating cellular behavior and aiding tissue regeneration. Investigations also highlight their potential in boosting athletic performance, especially through myocytes-derived exosomes that may enhance adaptability to physical training. Emphasizing a multidisciplinary approach, this review underlines the need to thoroughly understand exosome biology, including their pathways and classifications, to fully exploit their therapeutic potential. It outlines future directions in sports medicine, focusing on personalized treatments, clinical evaluations, and embracing technological advancements. This research represents a frontier in using exosomes to improve athletes' health and performance capabilities.